2011
DOI: 10.1021/ef200094h
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Modeling of Bitumen Hydroprocessing at In-Reservoir Conditions Employing Ultradispersed Catalysts

Abstract: Heavy oil and bitumen's low American Petroleum Institute (API) gravity and high viscosity make the economics of their industrialization difficult. Therefore, new recovery techniques must be developed to enhance these materials. Ultradispersed catalytic hydroprocessing of heavy oil and bitumen has been proposed as one of these novel techniques and has been tested in laboratories and pilot plants. In this work, a kinetic model for ultradispersed catalytic hydroprocessing of bitumen is proposed. Kinetic parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
43
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 21 publications
1
43
0
Order By: Relevance
“…For example, the values reported by Sánchez et al [12] indicated that the lighter the products from hydrocracking, the lower would be the activation energy for the hydrocracking reaction. On the other hand, the sequence of activation energies reported by Loria et al [14] and Martínez and Ancheyta [15] indicated that the lighter the products from hydrocracking, the higher would be the activation energy for hydrocracking reactions. The activation energies reported by Hassanzadeh and Abedi [13] showed no clear pattern.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the values reported by Sánchez et al [12] indicated that the lighter the products from hydrocracking, the lower would be the activation energy for the hydrocracking reaction. On the other hand, the sequence of activation energies reported by Loria et al [14] and Martínez and Ancheyta [15] indicated that the lighter the products from hydrocracking, the higher would be the activation energy for hydrocracking reactions. The activation energies reported by Hassanzadeh and Abedi [13] showed no clear pattern.…”
Section: Introductionmentioning
confidence: 99%
“…The model was originally proposed by Sánchez et al [12] for moderate hydrocracking of Maya heavy crude using Ni-Mo/c-Al 2 O 3 as catalyst at temperatures of 380-420°C, pressure of 6.9 MPa, and LHSV of 0.33-1.5 h À1 . Hassanzadeh and Abedi [13] used this model for kinetic modeling of in situ upgrading of heavy oil and bitumen in a batch reactor in the presence of Ni-W-Mo as dispersed catalysts at 320-380°C, pressure of 3.45 MPa, and residence times of 3-72 h. Loria et al [14] presented a five-lump kinetic model similar to that proposed by Sánchez et al [12] for hydroprocessing of bitumen at in-reservoir conditions using Ni-W-Mo dispersed catalysts in a tubular pilot plant reactor at 320-380°C, pressure of 2.76 MPa, and residence times of 9-51 h. Martínez and Ancheyta [15] used the same model for hydrocracking of an atmospheric residue in a continuous stirred basket reactor in the presence of a Ni-Mo catalyst at 380-420°C. To simplify the parameter estimation process, they modified the model into two, three and four-lump kinetic models and concluded that when various components were grouped in a single lump, the reaction kinetics was similar to the situation in which each lump had its own reaction pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A good prediction of the product yields was obtained with the proposed model, with an absolute average error (AAE) less than 5%. Loria et al [12] employed the five-lump kinetic model proposed by Sánchez et al [11] for the hydroprocessing of Athabasca bitumen processed in a tubular reactor, using Ni-Mo-W ultra dispersed catalysts. Reaction temperature and liquid hourly space velocity studied were 320-380°C and 0.09-0.2 h À1 respectively, at a constant pressure of 28 kg f /cm 2 and constant hydrogen-to-oil ratio of 3600 ft 3 /bbl.…”
Section: Introductionmentioning
confidence: 99%
“…For example, this knowledge is helpful in aerosol classification and its deposition under electrical fields, formation of deposits in heat exchangers and pipelines, hydrodynamic field chromatography, thrombus formation in organs and, many other areas (Adamczyk and Van De Ven, 1981). Recently, this phenomenon has gained particular importance on the dispersion of ultradispersed catalysts for heavy crude oil and bitumen hydroprocessing due to its practical significance and direct application Galarraga and Pereira-Almao, 2010;Loria et al, 2011). Ultradispersed catalysts have been studied for heavy oil and bitumen hydroprocessing as an alternative for typical supported catalysts.…”
Section: Introductionmentioning
confidence: 99%